Dominant‐negative mutation p.Arg324Thr in KCNA1 impairs Kv1.1 channel function in episodic ataxia. Issue 11 (1st August 2016) - Tristán‐Clavijo, Enriqueta; Scholl, Francisco G.; Macaya, Alfons; Iglesias, Gemma; Rojas, Ana M.; Lucas, Miguel; Castellano, Antonio; Martinez‐Mir, Amalia
ABSTRACT: Background: Episodic ataxia type 1 is a rare autosomal dominant neurological disorder caused by mutations in the KCNA1 gene that encodes the α subunit of voltage‐gated potassium channel Kv1.1. The functional consequences of identified mutations on channel function do not fully correlate with the clinical phenotype of patients. Methods: A clinical and genetic study was performed in a family with 5 patients with episodic ataxia type 1, with concurrent epilepsy in 1 of them. Protein expression, modeling, and electrophysiological analyses were performed to study Kv1.1 function. Results: Whole‐genome linkage and candidate gene analyses revealed the novel heterozygous mutation p.Arg324Thr in the KCNA1 gene. The encoded mutant Kv1.1 channel displays reduced currents and altered activation and inactivation. Conclusions: Taken together, we provide genetic and functional evidence that mutation p.Arg324Thr in the KCNA1 gene is pathogenic and results in episodic ataxia type 1 through a dominant‐negative effect. © 2016 International Parkinson and Movement Disorder Society